2020
DOI: 10.3390/polym12112584
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Synthesis of Castor Oil-Based Plasticizer and the Properties of Plasticized Nitrile Rubber

Abstract: A series of new environment-friendly plasticizers was synthesized from castor oil and used to plasticize nitrile rubber (NBR). The test results showed that tensile strength, elongation at break, and tear strength of NBR vulcanizates plasticized by castor oil-based plasticizers were found to be better than that of dioctyl phthalate (DOP). The aging test taken demonstrated that the castor oil-based plasticizers could improve the hot air and oil aging resistance of NBR vulcanizates. The thermal stability test ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…An improved thermal stability of the NBR vulcanizate with 4 phr SBOFA is clearly seen compared to that with no SBOFA, as also evident from the higher temperature of T 10% , T 50% , and T 90% . The higher thermal stability was possibly due to the interaction between the SBOFA and NBR [ 40 ]. Furthermore, it was observed in the temperature range of 500–800 °C the weight loss of the NBR with 4 phr SBOFA was gradually close to a straight line with the 6% of remaining weight, whereas that of the NBR without SBOFA further increased [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An improved thermal stability of the NBR vulcanizate with 4 phr SBOFA is clearly seen compared to that with no SBOFA, as also evident from the higher temperature of T 10% , T 50% , and T 90% . The higher thermal stability was possibly due to the interaction between the SBOFA and NBR [ 40 ]. Furthermore, it was observed in the temperature range of 500–800 °C the weight loss of the NBR with 4 phr SBOFA was gradually close to a straight line with the 6% of remaining weight, whereas that of the NBR without SBOFA further increased [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…The higher thermal stability was possibly due to the interaction between the SBOFA and NBR [ 40 ]. Furthermore, it was observed in the temperature range of 500–800 °C the weight loss of the NBR with 4 phr SBOFA was gradually close to a straight line with the 6% of remaining weight, whereas that of the NBR without SBOFA further increased [ 40 ]. This may be due to the SBOFA molecules acting as a protective barrier, which deterred the release of volatile degradation products out from the sample and suppressed the thermal degradation [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…They concluded that using the epoxy acetylated CO and epoxy benzoyl CO imparted the resulting NBR with better physico-mechanical and aging resistance properties than that with DOP. [13] Based on the previous results that showed that the modification of CO surface is a necessary step for producing rubber composite with superior physicomechanical properties, [15,16] we herein performed a modification to the CO but with gallic acid (GA) via an esterification reaction. GA, 3,4,5-trihydroxybenzoic acid, is a naturally occurring antioxidant found in a variety of vegetables and fruits.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 These characteristics make it a promising raw material for polymer additives, especially in PLA. Studies show the applicability of CO as a plasticizer, 14,15 lubricant, 16 and biofuel. 17 The wide application of CO is attributed to its chemical reactivity, being susceptible to various chemical modifications, 11,13 such as hydrogenation, transesterification, and epoxidation.…”
Section: Introductionmentioning
confidence: 99%